برنامج تدريبي مقترح لتنمية فعالية الذات الاعلامية لدى مستشاري التوجيه والارشاد المدرسي والمهني (دراسة ميدانية بمدينتي ورقلة وتقرت) - بالقاسمي, محمد الأزهر; خميس, عبد العزيز (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة الى الكشف عن برنامج تدريبي مقترح لتنمية فعالية الذات الاعلامية لدى مستشاري التوجيه والارشاد المدرسي والمهني بمدينتي ورقلة وتقرت خلال السنة الدراسية 2017-2018 حيث تم اعتماد المنهج التجريبي على عينة الدراسة متكونة من (30) مستشار ومستشارة بتصميم مجموعة تجريبية ضمت (15) مستشار ومجموعة ضابطة متكونة من 15 مستشار، حيث تلقى افراد المجموعة التجريبية تدريبا وفق جلسات ارادية من خلال برنامج ارشادي لتنمية الذات الاعلامية لديهم، وهذا بعد تطبيق مقياس فاعلية الذات الاعلامية، حيث تم اعتماد جملة من الاساليب الاحصائية المناسبة واستقرت الدراسة على النتائج الاتية: وجود فروق ذات دلالة احصائية في متوسطات درجات الافراد لمقياس فعالية الذات الاعلامية بين المجموعة الضابطة والمجموعة التجريبية بعد تطبيق البرنامج الارشادي المقترح لصالح المجموعة التجريبية. وجود فروق ذات دلالة احصائية في متوسطات درجات افراد المجموعة التجريبية لمقياس فعالية الذات الاعلامية بين القياس القبلي والقياس البعدي لصالح القياس البعدي ومن خلال ذلك بينت النتائج فعالية البرنامج التدريبي المقترح في تنمية فاعلية الذات لذى مستشاري الارشاد والتوجيه المدرسي. This study aimed to uncover a proposed training program for the development of the media self with counselors for school and vocational guidance and counseling in Madinaty and Ouargla, and it was decided during the 2017-2018 school year the experimental method was adopted on the study sample consisting of (30) consultants and consultants in designing an experimental group that included (15) A consultant and a control group consisting of 15 consultants, whereby the members of the experimental group received training according to voluntary sessions through an indicative program for the development of their media self, and this after applying the measure of the effectiveness of the media self, where a set of appropriate statistical methods were adopted and the study was inferred. The following results: There are statistically significant differences in individuals ’average scores to measure the effectiveness of the media self between the control group and the experimental group after applying the proposed indicative program in favor of the experimental group There are statistically significant differences in the mean scores of the members of the experimental group for the scale of the media self-efficacy between pre-measurement and post-measurement in favor of post-measurement. Through this, the results showed the effectiveness of the proposed training program in developing the effectiveness of the self for school counseling and guidance counselors.
A proposed training program to develop the effectiveness of the media self with the counselor of school and vocational guidance and counseling (A field study in the cities of Ouargla and Touggourt)
مقال
Keywords: برنامج ارشادي؛ تنمية؛ فعالية الذات؛ فعالية الذات الاعلامية؛ مستشار التوجيه.; Heuristic program; development; Self-efficacy; Informational self-efficacy; Guidance Counselor